Negotiating the Cultural Identity of Expatriate Teachers in the Cooperation Education Unit - Kristina Nurhayati; Mirza Ronda; Titi Widaningsih (Journal of Social Science, 2022)
The phenomenon of international communication (Cross-Cultural) in the field of education is increasingly in demand, especially in the era of globalization. This study aims to describe, understand and find negotiations on the cultural identity of expatriate teachers in cooperative education units (SPK), especially Filipino teachers in their interactions. This research uses a constructivist paradigm and a qualitative approach using the phenomenological method.This study observes the social interactions of Filipino expatriates in the context of intercultural communicators using Face Negotiation theory with 3 key concepts, namely Cultural Identity, Communication Behavior and Facework.Cultural identity in this research is the details of the characteristics or characteristics of a culture that is owned by a group of people whose boundaries are known when compared to the characteristics or characteristics of other cultures. Cultural identity referred to in this study is either scripted or non-scripted communication behavior, this form of behavior is related to the daily life of the individual. And facework in this study focuses more on human communication behavior that is used to build and protect their appearance as well as to protect, build and threaten the faces of others.